STUDIES ON MORPHOLOGY OF MANGO ANTHRACNOSE DISEASE CAUSING FUNGUS COLLETOTRICHUM GLOEOSPORIOIDES (PENZ.) PENZ. AND SACC. AND EFFICACY OF AZOXYSTROBIN AGAINST THE FUNGUS UNDER IN VITRO AND IN VIVO CONDITION - N. K. ADHIKARY; S. DEY; J. TARAFDAR (The Bioscan, 2013)
Anthracnose disease caused by Colletotrichum gloeosporioides is one of the most serious diseases causing yield losses in mango. For controlling this disease much of attention and efforts has concentrated on the application of fungicides. The indiscriminate use of different fungicides possesses potential threat to human health, phytotoxicity, environmental hazards and development of pathogen resistance. Keeping this in view, the efficacy of azoxystrobin, one of the strobilurin class fungicides, which has broad-spectrum activity against large number of plant diseases, was evaluated both under in vitro and in vivo conditions. In in vitro tests, azoxystrobin significantly reduced both mycelial growth and conidial germination of C. gloeosporioides in PDA media. Although the mycelial growth and conidial germination of the fungus was declined continuously in 100, 200, 300 and 400ppm, the optimum rate was obtained at 100ppm where it responded continuously to climb with increasing rates. In field experiment, azoxystrobin treated trees showed lesser leaf anthracnose than control. The reduction of anthracnose intensity and yield increased curve obtain, shows flattening between the range 100 and 400ppm concentrations, hence the optimum rate of azoxystrobin was fixed to be at 100ppm for the control of anthracnose disease.